Hfe deficiency impairs pulmonary neutrophil recruitment in response to inflammation - Gente, Karolina; Spasić Vujić, Maja; Schäfer, Sebastian Markus; Stolte, Jens; Baehr-Ivacevic, Tomi; Waldow, Katharina; Zhou-Suckow, Zhe; Klingmüller, Ursula; Benes, Vladimir; Mall, Marcus A.; Muckenthaler, Martina (PLOS ONE, 2012)
Regulation of iron homeostasis and the inflammatory response are tightly linked to protect the host from infection. Here we investigate how imbalanced systemic iron homeostasis in a murine disease model of hereditary hemochromatosis (Hfe−/− mice) affects the inflammatory responses of the lung. We induced acute pulmonary inflammation in Hfe−/− and wild-type mice by intratracheal instillation of 20 µg of lipopolysaccharide (LPS) and analyzed local and systemic inflammatory responses and iron-related parameters. We show that in Hfe−/− mice neutrophil recruitment to the bronchoalveolar space is attenuated compared to wild-type mice although circulating neutrophil numbers in the bloodstream were elevated to similar levels in Hfe−/− and wild-type mice. The underlying molecular mechanisms are likely multifactorial and include elevated systemic iron levels, alveolar macrophage iron deficiency and/or hitherto unexplored functions of Hfe in resident pulmonary cell types. As a consequence, pulmonary cytokine expression is out of balance and neutrophils fail to be recruited efficiently to the bronchoalveolar compartment, a process required to protect the host from infections. In conclusion, our findings suggest a novel role for Hfe and/or imbalanced iron homeostasis in the regulation of the inflammatory response in the lung and hereditary hemochromatosis.
Gesehen am 09.04.2018